Pengaruh Informasi Akuntansi, Likuiditas, Leverage Terhadap Harga Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Anggraini Agustina; Nur Diana; Dewi Diah Fakhriyyah (Universitas Islam Malang, 2023)
The phenomena of this research is the increase in investment in the manufacturing sub-sector that occurred in the 2021-2022 period. The increase in investment that occurs indicates an increase in investment that occurs on the Indonesian stock exchange so that it will have an impact on increasing stock prices. The increase in stock prices that occur can be influenced by several factors such as accounting information, liquidity, leverage so that in this study it can be explained whether accounting information, liquidity, leverage affect stock prices. The purpose of this study was to determine the effect of accounting information, liquidity, leverage on stock prices in manufacturing companies. Signal theory is the theory used in this study because signal theory is an action taken by a company to provide clues to investors about the company's prospects. The method in this study uses quantitative. Data collection uses the documentation method by taking financial report data published by manufacturing companies on the Indonesian stock exchange for the 2018-2021 period. Three hypotheses were tested using multiple linear regression analysis. The results of this study indicate that accounting information, liquidity, and leverage affect stock prices in manufacturing companies listed on the Indonesian stock exchange in 2018-2021Keywords: Accounting information, liquidity, leverage, stock price, signal theory